Integrated Assessment of Rooftop Photovoltaic Systems and Carbon Footprint for Organization: A Case Study of an Educational Facility in Thailand - Nattapon Leeabai; Natthakarn Sakaraphantip; Neeraphat Kunbuala; Kamonchanok Roongrueng; Methawee Nukunudompanich (Energies)
This study presents an integrated methodology to assess and reduce greenhouse gas (GHG) emissions in institutional buildings by combining organizational carbon footprint (CFO) analysis with rooftop photovoltaic (PV) system simulation. The HM Building at King Mongkut’s Institute of Technology Ladkrabang (KMITL), Thailand, was selected as a case study to evaluate carbon emissions and the feasibility of solar-based mitigation strategies. The CFO assessment, conducted in accordance with ISO 14064-1:2018 and the Thailand Greenhouse Gas Management Organization (TGO) guidelines, identified total emissions of 1841.04 tCO2e/year, with Scope 2 electricity-related emissions accounting for 442.00 tCO2e/year. Appliance-level audits revealed that classroom activities represent 36.7% of the building’s electricity demand. These findings were validated using utility data totaling 850,000 kWh/year. A rooftop PV system with a capacity of 207 kWp was simulated using PVsyst software (version 7.1), incorporating site-specific solar irradiance and technical loss parameters. Monocrystalline modules produced the highest energy output of 292,000 kWh/year, capable of offsetting 151.84 tCO2e/year, equivalent to 34.4% of Scope 2 emissions. Economic evaluation indicated a 7.4-year payback period, with a net present value (NPV) of THB 12.49 million and an internal rate of return (IRR) of 12.79%. The integration of verified CFO data with empirical load modeling and derated PV performance projections provides a robust, scalable framework for institutional carbon mitigation. This approach supports data-driven Net Zero campus planning aligned with Thailand’s Nationally Determined Contributions (NDCs) and carbon neutrality policies.